KEPERCAYAAN GAIB DAN KEJAWEN Studi Kasus pada Masyarakat Pesisir Kabupaten Rembang Ikha Safitrf Perencanaan dan Pengelolaan Sumberdaya Kelautan Program Magister Manajemen Suniberdaya Pantai Universitas Diponegoro Abstract - Safitrf, Ikha (Sabda: Jurnal Kajian Kebudayaan, 2013)
This paper discusses supernatural belief and Kejawen (the Javanese teaching), a case study on coastal society in Rembang Regency, Central Java. The people in the society believe in supernatural creatures possessing the power to do particular works intended to help, or even to disturb and to hurt other people. The people embrace Kejawen Islam, which is a mixed belief of the native Javanese religious custom (animism and dynamism) and Buddhist-Hindu in the era ofMajapahit Kingdom and the influence of Islam m the era of Demak Kingdom.